2011
DOI: 10.1002/jmri.22435
|View full text |Cite
|
Sign up to set email alerts
|

Active Crohn's Disease in the small bowel: Evaluation by diffusion weighted imaging and quantitative dynamic contrast enhanced MR imaging

Abstract: Purpose: To determine relative diagnostic value of MR diffusion and perfusion parameters in detection of active small bowel inflammation in patients with Crohn's disease (CD). Materials and Methods:We reviewed 18 patients with active CD of terminal ileum (TI) who underwent MR enterography (MRE; including dynamic contrast enhanced MRI and diffusion-weighted MRI). Conventional MRI findings of TI were recorded. Regions of interest were drawn over TI and normal ileum to calculate apparent diffusion coefficient (AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
130
2
5

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 192 publications
(142 citation statements)
references
References 36 publications
(55 reference statements)
5
130
2
5
Order By: Relevance
“…well-known imaging features are evaluated using a combination of unenhanced and post-contrast T1-weighted images, usually with fat suppression, T2-weighted images with and without fat suppression, and more recently diffusion-weighted images [16][17][18][19]. However, there are times when these sequences are not completely diagnostic for inflammatory bowel disease, and having additional imaging criteria would be useful.…”
mentioning
confidence: 99%
“…well-known imaging features are evaluated using a combination of unenhanced and post-contrast T1-weighted images, usually with fat suppression, T2-weighted images with and without fat suppression, and more recently diffusion-weighted images [16][17][18][19]. However, there are times when these sequences are not completely diagnostic for inflammatory bowel disease, and having additional imaging criteria would be useful.…”
mentioning
confidence: 99%
“…The potential of DCE-MRI as a biomarker for measuring antiangiogenic effects of cancer therapy can also be used in bowel imaging for evaluating the vascularization of intestinal segments and likewise for evaluating therapy response in both chronic inflammatory bowel diseases and in tumors of the bowel [49,50]. In a study involving 18 patients, Oto et al showed that combining DCE-MRI with new methods of diffusion-weighted imaging (DWI) provides a good quantitative measure for differentiating acutely inflammatory changes in the small intestine from normal intestinal segments [35]. However, DWI was even superior to DCE-MRT in this endeavor.…”
Section: Dynamic Contrast Enhanced (Dce) Mrimentioning
confidence: 99%
“…The technique may be useful in determining pathology in the liver (degree of cirrhosis/fibrosis), kidneys (lesion characterization, renal failure, pyelonephritis), pancreas (pancreatitis and pancreatic cancer), bowel (Crohn's disease), and uterus (endometriosis) [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] . In a recent meta-analysis, Li et al [19] has shown a potential future role for this type of sequence to assess for cancers within the liver.…”
Section: Introductionmentioning
confidence: 99%